Timescale of hole closure during plasma membrane repair estimated by calcium imaging and numerical modeling - Martin Berg Klenow; Anne Sofie Busk Heitmann; Jesper Nylandsted; Adam Cohen Simonsen (Scientific Reports, 2021)
Abstract Plasma membrane repair is essential for eukaryotic cell life and is triggered by the influx of calcium through membrane wounds. Repair consists of sequential steps, with closure of the membrane hole being the key event that allows the cell to recover, thus identifying the kinetics of hole closure as important for clarifying repair mechanisms and as a quantitative handle on repair efficiency. We implement calcium imaging in MCF7 breast carcinoma cells subject to laser damage, coupled with a model describing the spatio-temporal calcium distribution. The model identifies the time point of hole closure as the time of maximum calcium signal. Analysis of cell data estimates the closure time as: $$\langle t_c \rangle =5.45± 2.25$$ ⟨ t c ⟩ = 5.45 ± 2.25 s and $$\langle t_c \rangle =6.81± 4.69$$ ⟨ t c ⟩ = 6.81 ± 4.69 s using GCaMP6s-CAAX and GCaMP6s probes respectively. The timescale was confirmed by independent time-lapse imaging of a hole during sealing. Moreover, the analysis estimates the characteristic time scale of calcium removal, the penetration depth of the calcium wave and the diffusion coefficient. Probing of hole closure times emerges as a strong universal tool for quantification of plasma membrane repair